Integrasi Disiplin Keilmuan Di Tingkat Perguruan Tinggi - Naufal Habibi; Ristiawan Nazar (Interdisciplinary Explorations in Research Journal, 2023)
Abstract Social and Humanities is an academic discipline that studies broad social and cultural aspects of humanity. At the tertiary level, social and humanities play an important role in teaching and research in the humanities, social sciences, culture, literature and philosophy. Through a social sciences and humanities approach, students can study various social, political, cultural and environmental issues, as well as ways to solve social problems and improve the quality of human life. These programs usually include studies on regional social and cultural issues, political science, philosophy, philology, and literature. Some examples of these programs that can be offered include communication sciences, anthropology, political science, philosophy, and contemporary thought. Keywords: Integration, Course, Social, University Abstrak Sosial dan Humaniora adalah disiplin akademis yang mempelajari aspek-aspek sosial dan budaya yang luas dari kemanusiaan. Di tingkat tersier, ilmu sosial dan humaniora memainkan peran penting dalam pengajaran dan penelitian di bidang humaniora, ilmu sosial, budaya, sastra, dan filsafat. Melalui pendekatan ilmu sosial dan humaniora, mahasiswa dapat mempelajari berbagai masalah sosial, politik, budaya dan lingkungan, serta cara-cara untuk memecahkan masalah sosial dan meningkatkan kualitas hidup manusia. Program-program ini biasanya mencakup studi tentang isu-isu sosial dan budaya regional, ilmu politik, filsafat, filologi, dan sastra. Beberapa contoh program yang dapat ditawarkan antara lain ilmu komunikasi, antropologi, ilmu politik, filsafat, dan pemikiran kontemporer. Kata kunci: Integrasi, Program, Sosial, Universitas